Even greater mistakes - Anders, Charlie Jane (Tor, 2021)
"In her short story collection, Even Greater Mistakes, Charlie Jane Anders upends genre cliches and revitalizes classic tropes with heartfelt and pants-wettingly funny social commentary. The woman who can see all possible futures is dating the man who can see the one and only foreordained future. A wildly popular slapstick filmmaker is drawn, against his better judgment, into working with a fascist militia, against a background of social collapse. Two friends must embark on an Epic Quest To Capture The Weapon That Threatens The Galaxy, or else they'll never achieve their dream of opening a restaurant. The stories in this collection, by their very outrageousness, achieve a heightened realism unlike any other. Anders once again proves she is one of the strongest voices in modern science fiction, the writer called by Andrew Sean Greer, "this generation's Le Guin.""--